STUDY OF THE PERSONALITY OF A CHILD WITH MENTAL DEVELOPMENTAL DELAY USING THE HOUSE-TREE-PERSON PROJECTIVE TECHNIQUE - Yulia T. Antonova; Ayyna I. Vinokurova; Diana I. Permyakov (Russian Journal of Education and Psychology)
Background. The article is dedicated to the use of projective techniques in the diagnosis of children with mental developmental delays. It highlights that initiating diagnostic assessments for these children is driven not only by challenges in mastering the school curriculum but also by difficulties in emotional regulation and building interpersonal relationships.